A Multiplexed Assay That Monitors Effects of Multiple Compound Treatment Times Reveals Candidate Immune-Enhancing Compounds. (August 2018) - Zhao, Ziyan; Henowitz, Liza; Zweifach, Adam
We previously developed a flow cytometry assay that monitored lytic granule exocytosis in cytotoxic T lymphocytes stimulated by contacting beads coated with activating anti-CD3 antibodies. That assay was multiplexed in that responses of cells that did or did not receive the activating stimulus were distinguished via changes in light scatter accompanying binding of cells to beads, allowing us to discriminate compounds that activate responses on their own from compounds that enhance responses in cells that received the activating stimulus, all within a single sample. Here we add a second dimension of multiplexing by developing means to assess in a single sample the effects of treating cells with test compounds for different times. Bar-coding cells before adding them to test wells lets us determine compound treatment time while also monitoring activation status and response amplitude at the point of interrogation. This multiplexed assay is suitable for screening 96-well plates. We used it to screen compounds from the National Cancer Institute, identifying several compounds that enhance anti-LAMP1 responses. Multiple-treatment-time (MTT) screening enabled by bar-coding and read via high-throughput flow cytometry may be a generally useful method for facilitating the discovery of compounds of interest.